A Study of Graph Theory Applications in IT Security - Khaleel, Turkan Ahmed; Al-Shumam, Ayhan Ahmed (Iraqi Journal of Science, 2020)
The recent developments in information technology have made major changes in all fields. The transfer of information through networks has become irreplaceable due to its advantages in facilitating the requirements of modern life through developing methods of storing and distributing information. This in turn has led to an increase in information problems and risks that threaten the security of the institution’s information and can be used in distributed systems environment. This study focused on two parts; the first is to review the most important applications of the graph theory in the field of network security, and the second is focused on the possibility of using the Euler graph as a Method Object that is employed in Remote Method Invocation (RMI) technique. This algorithm was compared with the most popular algorithms, such as RSA and 3DES. The results were acceptable and need to be improved in the future.